A qualitative comparison evaluation of the greedy forwarding strategies in mobile ad hoc network - Al-shugran, Mahmoud; Ghazali, Osman; Hassan, Suhaidi; Nisar, Kashif; Che Mohamed Arif, Ahmad Suki (Elsevier B.V., 2013)
The Mobile Ad Hoc Network (MANET) is wireless network which provides communication among wireless mobile hosts without the need of any standing network infrastructure.In such networks, and to facilitate communication between participating nodes, every node has to offer routing services.Routing in MANET is responsible for selecting and forwarding packets along optimal paths.Finding an optimal route is a crucial task in MANET where routes tend to be multi-hop. Many routing protocols have been proposed in literature. However, few of them are efficient when the network is sparse and highly dynamic.Position-based routing and forwarding provides the opportunity for improving the efficiency and performance of the existing MANET routing strategies. This research work presents an extensive overview of geographic forwarding techniques in MANET. In particular, it focuses on the presentation of the basic operation mode of geographic forwarding, which is greedy forwarding. Meanwhile, this research work presents a qualitative evaluation of the most current and popular greedy forwarding strategies used with position based routing protocols. Furthermore, the findings have been used to conclude the most appropriate unicast forwarding policy for future research efforts.